Perceptions of Cross-Cultural Challenges and Successful Approaches in Facilitating the Improvement of Equine Welfare - Suzanne Rogers; Natasha Y. P. Lee; Jo White; Catherine Bell (Animals, 2023)
Projects that aim to improve the welfare of equids worldwide usually involve people from different countries and cultures working together. Given that professionals involved with multi-stakeholder projects often work cross-culturally, this study examined their experiences regarding the challenges involved in, and their reflections on, how to work in a culturally sensitive way. Semi-structured interviews were conducted with 14 participants working in a total of 29 countries and analysed using thematic analysis. Key response themes emerged from the responses to questions covering the areas of perceptions of animal welfare, challenges working cross-culturally and embracing cultural sensitivity. The overriding theme regarding perceptions of animal welfare was that of barriers to animal welfare, under which emerged the subthemes of limited financial and material resources, limited understanding of the tenets of animal welfare, and attachment to traditional medicines and practices. Exploring the key challenges resulted in two themes: challenges regarding the local context and etiquette, and those regarding working with different stakeholders. Considering cultural sensitivity, again, two themes emerged: the importance of trust and respect, and of working with local partners. Previous works have highlighted the importance of shared linguistic knowledge, interpersonal skills and cultural knowledge, and these elements also emerged in this research. As well as providing insights into the challenges of working cross-culturally, the findings of this study have enabled the development of suggestions for how this work could be taken forward in a practical way to be of use to professionals in this sector.